Criminal Liability of Police Officers in Cases of Abuse of Authority Against Protesters - Sri Setiawati; Sumartini Dewi (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
The misuse of authority by law enforcement officers in handling public demonstrations remains a recurring issue within Indonesia’s legal enforcement practices. Such incidents are frequently manifested through arbitrary arrests, excessive use of force, and the criminalization of peaceful protesters. In fact, the right to express opinions publicly is explicitly guaranteed under the 1945 Constitution and Law No. 9 of 1998. Repressive actions of this nature not only constitute legal violations but also erode public trust in the police institution. From a criminal law perspective, officers who exceed their authority may be held accountable under provisions of the Indonesian Penal Code, such as Article 170 or 351 on acts of violence, as well as through internal disciplinary sanctions. This study employs both normative and empirical approaches, examining recent cases including the May Day 2025 demonstrations and the Kanjuruhan tragedy to highlight weaknesses in oversight mechanisms, both internal and external. Findings indicate that a culture of impunity persists, allowing officers to often escape criminal liability despite evidence of misconduct. Therefore, comprehensive reforms are urgently needed, including strengthening oversight systems, ensuring consistent law enforcement, and fostering cultural transformation within the police force to ensure accountability and justice are genuinely upheld.